Formic acid pretreatment of lignin to facilitate the depolymerization of lignin by laccase from trametes versicolor - Nurul Shafiqha, Mohd Rudzelan (2016)
This article presents an exhaustive review of these studies and suggests a direction for future developments. The utilization of lignin for production of molecular aromatic chemicals has become an effective alternative way instead of using petroleum. An experimental investigation was conducted to study the effect of formic acid on the pretreatment of lignin from palm oil empty fruit bunch (POEFB) by varies the reaction time and explore the effect of formic acid pretreatment on lignin depolymerization by laccase from Trametes versicolor (LTV). 100 ml of formic acid solution with 0.2M H2SO4 as a catalyst was used to pretreat lignin from POEFB at different residence times. Laccase assay was determined based on 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) concentration. The depolymerization of lignin was conducted by using lignin from POEFB depolymerize by LTV and mediated by ABTS. The products were separated by fractionation method and had been analyzed by using High Performance Liquid Chromatography (HPLC). The LTV activity demonstrates the higher performance when the concentration of ABTS was 1.0 mM. As the concentration of ABTS increase, the rate of reaction of LTV was also increase. Vanillin was expected to be produced at the end of the research, however by comparing the average retention time of vanillin with samples, the peak observed was not representing the vanillin. On the other hand, the peak was representing unknown chemical compound.